Chemotherapy-associated oral microbiome changes in breast cancer patients - Klymiuk, Ingeborg; Bilgilier, Ceren; Mahnert, Alexander; Prokesch, Andreas; Heininger, Christoph; Brandl, Ingeborg; Sahbegovic, Hanka; Singer, Christian; Fuereder, Thorsten; Steininger, Christoph (Frontiers in Oncology, 2022)
Cytotoxic chemotherapy with or without combination of humanized monoclonal antibodies is regarded as the gold standard of personalized medicine for the treatment of breast cancer patients. Significant medication-related side effects are common accompanying phenomena for these patients, such as oral discomfort, mucositis or even osteonecrosis of the jaw. In this study, we analyze saliva samples of 20 breast cancer patients at three time points throughout their chemotherapy: at baseline prior to treatment initiation (T1), after four to six cycles of chemotherapy (T2) and one year after start of the treatment (T3) to investigate and characterize the long-term effects of the chemotherapy n the oral microbiome. We aimed to characterize changes in the oral, bacterial microbiome based on 16S rRNA gene amplicon analysis during chemotherapeutic treatment, as a potential target to treat common oral side effects occurring during therapy. Chemotherapeutic drugs used in our study for patient treatment were Trastuzumab, Docetaxel, Pertuzumab, Epirubicin and Cyclophosphamide. We find a significant increase in relative abundance of potentially pathogenic taxa like Escherichia/Shigella and non-significant trends in the relative abundance of e.g. Actinomyces ssp. In conclusion, the role of microbiota in oral side effects of chemotherapeutic treatment needs to be considered and should be analyzed in more detail using larger patient cohorts. Oral side effects in breast cancer patients undergoing chemotherapy are a common burden and should be treated for a better tolerability of the therapy.